Evaluating the Implementation of Standard Operating Procedure (SOP) According to Knowledge Management (Case Study of Bank Keluarga’s Frontliner) - Arip Hermawan Dwi Saputro; Madju Yuni Ros Bangun (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Knowledge has various forms, one of which is the Standard Operating Procedure (SOP). The number of SOPs will be directly proportional to the company's growth. The more a company grows, the more it will increase the number of SOPs or will cause more changes or adjustments to SOPs. During 2008 – 2016 Bank Keluarga expanded its business by adding Wholesale, Sinaya, Mitra Usaha Rakyat, Mitra Bisnis, WOW!, and Jenius. Each line of business has its own branch specifically to serve the segment it covers. Gemilang Project with Branch Integration as one of its initiatives then integrates the services of each line of business into one universal branch and to allow service across lines of business. However, the facts that 54% of frontliners received below standard Branch Quality Assessment Rating and 68% of branches received an average and below standard Branch Assessment rating make it necessary to to evaluate the implementation of SOP according to the knowledge management system especially in frontliner of Bank Keluarga. Primary data collected using questionnaires then SPSS Statistical Software 26 version has used to analyze the data. The result of the research obtained that Leadership and Learning are the only two variables that significantly affect the outcome.